Provisions in Metallurgical Industry and Financial Crisis - Michal Bobek (European Financial and Accounting Journal, 2013)
The article studies the provisions in the metallurgical industry – the number of financial statements disclosing provisions and the amount of provisions disclosed in financial statements. The aim of article is both to presents the provisions disclosed in the financial statements and to determine the influence of financial crisis on the disclosing of provisions in this industry. The individual types of provisions are analyzed as well. The individual types of provisions are researched concerning the number of disclosed provisions and amount of them.
Keywords: M19; M41; 650; Provisions; Metallurgical Industry; Financial crisis; Czech Republic